Sustainability in Action: Corporate Social Responsibility Practices at Google LLC - Upadhayay , Sugam; Prajapati, Dinesh; Alqassimi, Omaima; Gopali, Rupendra (Journal of Entrepreneurship & Management Studies, 2025)
The paper examines the corporate social responsibility (CSR) practices and sustainability strategies employed by Google LLC, one of the world’s most influential technology companies. Underpinned by stakeholder theory and triple bottom line framework, the paper assesses Google’s approach to integrating CSR across its business operations and corporate strategies. It emphasizes the company’s trajectory from traditional philanthropy to sustainability-oriented approaches across environmental, social and ethical governance. Google’s CSR efforts include carbon neutrality, investment in renewable energy and multiple social impact projects through Google.org. The analysis considers criticism of Google’s CSR, including allegation of greenwashing and data privacy issues. The findings reveal that CSR at Google is not only a moral and social obligation but also a strategic business function, enhancing long-term competitiveness while promoting global well-being. At the same time, it highlights the significance of embedding sustainability into corporate DNA. Actionable recommendations are provided for CSR leadership, alignment of goals, stakeholder collaboration, accountability, and transparency.